Peningkatan Kemampuan Pemecahan Masalah Matematis Siswa Melalui Model Pembelajaran Dircursus Multy Reprecentation Pada Mata Pelajaran Matematika di Sekolah Dasar - Nurhidayati, Anindhita; Mahpudin (Papanda Publisher, 2023)
Primary research related to the implementation of Discourse Multi Representation (DMR) to improve students' mathematical problem solving abilities has been carried out a lot. These studies need to be identified, their developments analyzed, and general conclusions drawn so that they can be used as suggestions for the progress of researchers and practitioners in the field of education. This study aims to look at research trends by identifying and classifying all research results related to the application of the Discourse Multi Representation (DMR) model to improve students' mathematical problem solving skills in Indonesia in 2018-2022. This study uses the Systematic Literature Review (SLR) method. There are 7 related articles analyzed in this study. The results of this SLR show that the most research on the implementation of the Discourse Multi Representation (DMR) learning model on students' mathematical problem solving abilities was mostly carried out in 2021 and the most research subjects were elementary students. The most widely used research method is the quantitative method and in general the results show that the Discursus Multy Reprecentation (DMR) model is able to have a positive impact or improve students' mathematical problem solving skills compared to other learning models. The results of this study can be a consideration for researchers in conducting research and for teachers in carrying out learning in the classroom